(untitled) (Al Insyirah International Scientific Conference on Health, 2021)
Coping mechanism is one of the ways that is done to adapt to stress. Coping mechanisms used by hemodialysis patients are problem-centered coping i.e. confrontation and problem solving, emotionally centered coping such as seeking social support, acceptance, distance keeping, self-control. The research design to be used is descriptive. With the technique of sampling is a purposive sample where the number of sam is as many as 78 people. The results of the study known coping mechanism Coping mechanism chronic renal failure patients who followed hemodialysis therapy majority maladaptive as many as 49 people (62.8%) adaptive 29 people (37.2%). It is recommended that nurses educate new patients or older patients to continue to provide education to maintain adaptive individual coping, and to be able to change the perception of maladaptive individuals.